2023
DOI: 10.22541/essoar.167591099.90276751/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Impacts of Energy and Vehicle Transformation through 2050 on the Atmospheric Environment of Japan: focus on PM2.5 Metals and Aerosol Acidity inducing Respiratory Inflammation

Abstract: The impacts of renewable energy shifting, passenger car electrification, and lightweighting through 2050 on the atmospheric concentrations of PM2.5 total mass, Fe, Cu, and Zn, and aerosol acidity in Japan were evaluated using a regional meteorology–chemistry model. We focus on the changes in on-road exhaust/non-exhaust and upstream emissions. The domestic primary emissions of PM2.5, Fe, Cu, and Zn were reduced by 9%, 19%, 18%, and 10%, and their surface concentrations in the urban area decreased by 8%, 13%, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…In another paper, we estimated vehicle powertrain and energy mix in 2050 assuming that the Japanese government's target for the share of renewable energy and next generation vehicles (BEV, Hybrid Electric Vehicle; HEV, Plug in Hybrid Electric Vehicles; PHEV and Fuel Cell Vehicle; FCV) are met. The results suggested that the external charging electricity for BEVs and PHEVs in 2050 could be covered by surplus electricity from solar power generation if whole surplus electricity could be utilized without discarding (Kayaba & Kajino, 2023). That is, in such a realistic future scenario, little or no increase in power plant emissions in the upstream process may occur.…”
Section: Methodsmentioning
confidence: 99%
“…In another paper, we estimated vehicle powertrain and energy mix in 2050 assuming that the Japanese government's target for the share of renewable energy and next generation vehicles (BEV, Hybrid Electric Vehicle; HEV, Plug in Hybrid Electric Vehicles; PHEV and Fuel Cell Vehicle; FCV) are met. The results suggested that the external charging electricity for BEVs and PHEVs in 2050 could be covered by surplus electricity from solar power generation if whole surplus electricity could be utilized without discarding (Kayaba & Kajino, 2023). That is, in such a realistic future scenario, little or no increase in power plant emissions in the upstream process may occur.…”
Section: Methodsmentioning
confidence: 99%